Satguru's Word, Online and Offline. Issue 1 (2nd November 2021) - Bochkovskaya, Anna
Abstract : This essay discusses offline and online representation of the Avtar Bani—a controversial sacred text of the Sant Nirankari Mission ("Universal Brotherhood") listed by mainstream Sikh authorities as one of the six most "dangerous" religious organizations/sects in present-day India, which is understood to undermine the religious and moral values of Sikhs. Since its publication in 1957, the Avtar Bani has been used by Sant Nirankaris as an alternative to the Guru Granth—the sacred scripture of Sikhism. Mainstream Sikhs consider the Avtar Bani derogatory to the Sikh faith and demand that it be banned by the Punjab government. Nevertheless, copies of the text are kept in Sant Nirankari temples in Punjab and beyond; and yet, unlike the Sikh scripture, they have never been iconized. In the past decade, online representation of the book has become quite popular owing to Sant Nirankari Mission's efforts to use digital technologies for promoting its ideology, especially among the Punjabi diaspora.